(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Face Recognition is a widely used research area that is being carried out by researchers in order to use it in different areas. The reason is its sole importance in a number of applications like face detection in crime scenes by the videos of the CCTV cameras, biometrics, authentication in customer relationship etc. A problem that arises in face recognition is that because of complex features like wrinkles, facial expressions, aging, the face of a person is sometimes not recognized by the system. If a fine approach is achieved which can estimate the correct age of a person despite of the aging factors which affect the image, then most of the problems in the face recognition would be solved. This review paper provides a detailed survey of the various state of art techniques of age estimation which are helpful in face recognition.